การผสมผสานวิถีการปฏิบัติและประเพณีทางศาสนาของพุทธศาสนิกชนในบริบทพื้นที่ชายแดนไทยและเมียนมา - ภัทรสุดา สาลีวรรณ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2016)
This research was conducted by using two main methodologies: documentary research and field research. Firstly, the study aimed to find out the historical documents from the National Archives and from local key informants. Secondly, its field research applied the qualitative research by approaching participant observation and in-depth interview as its two main methods to collect data from the key informants at Tambon Thasailuad in Maesot district, Tak province. The research site was selected because it is located along the border area between Thailand and Myanmar, having Myanmar temples as well as having Thai and Myanmar monks and laypeople to live and practice Buddhism together in the area. The research found that Maesot is a multicultural society having both Thai and Myanmar cultures interacted and coexisted. It can clarify their religious acculturation as 3 patterns. Firstly, the development and utilization of religious spaces and architecture are tentatively in the approach of acculturation through Myanmar Buddhist culture. This is mainly because in Maesot there are more religious Myanmar laypeople than Thai ones. The Myanmar laypeople are also the larger group of donators who construct all religious things in Thai and Myanmar monasteries. Secondly, religious practices of Myanmar monks have to follow the Thai Sangha act. It is therefore quite obvious that the Myanmar monks in Maesot have tried to acculturate their religious practices and rituals into the Thai customs. However, the Thai monks have also adapted Myanmar practices and attended some Myanmar Buddhist ceremonies. Thirdly, the religious practices and customs of Thai laypeople are more tentatively acculturated into the Myanmar culture than those of Myanmar laypeople. This is certainly because although both Thai and Myanmar laypeople have similarly strong faith and beliefs in Buddhism, there are more Myanmar laypeople than the Thai ones in Thasailuad. It means that the lay Buddhist practices tend to follow the Myanmar culture. But, both Thai and Myanmar lay Buddhist practices and customs can be acculturated to each other, and can make them as the local Maesot Buddhist identity The research reveals how Maesot is the multicultural society where both Thai and Myanmar monks and laypeople can live together peacefully. They have good relationship based on their related Theravadin Buddhist beliefs and practices. This pattern of religious acculturation is as important as an elementary model for strengthening the ASEAN Socio-Cultural Community in the near future.